God? Very probably : five rational ways to think about the question of God - Nelson, Robert H. (Robert Henry), 1944- (The Lutterworth Press, 2016)
Drawing on a range of recent developments in science and theology, this book develops a new case for the rationality of believing in the existence of a monotheistic god.